The role of immunotherapy in microsatellites stable metastatic colorectal cancer: state of the art and future perspectives - Gandini, Annalice; Puglisi, Silvia; Pirrone, Chiara; Martelli, Valentino; Catalano, Fabio; Nardin, Simone; Seeber, Andreas; Puccini, Alberto; Sciallero, Stefania (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is the third leading cause of cancer-related deaths worldwide, despite several advances has been achieved in last decades. Few prognostic and predictive biomarkers guide therapeutic choice in metastatic CRC (mCRC), among which DNA mismatch repair deficiency and/or microsatellite instability (dMMR/MSI) holds a crucial role. Tumors characterized by dMMR/MSI benefit from immune checkpoint inhibitors. However, most of the mCRC patients (around 95%) are microsatellite stable (MSS), thereby intrinsically resistant to immunotherapy. This represents a clear unmet need for more effective treatments in this population of patients. In this review, we aim to analyze immune-resistance mechanisms and therapeutic strategies to overcome them, such as combinations of immunotherapy and chemotherapy, radiotherapy or target therapies specifically in MSS mCRC. We also explored both available and potential biomarkers that may better select MSS mCRC patients for immunotherapy. Lastly, we provide a brief overview on future perspectives in this field, such as the gut microbiome and its potential role as immunomodulator.